2013
DOI: 10.1126/scitranslmed.3006468
|View full text |Cite
|
Sign up to set email alerts
|

Genomics in Clinical Practice: Lessons from the Front Lines

Abstract: This Commentary explores the challenges in launching a medical genomics clinic for whole genome sequencing and analysis of patient samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 19 publications
(15 reference statements)
0
76
1
Order By: Relevance
“…This level of yield is similar to or slightly higher than those of previous reports, either in research studies 1,[5][6][7] or clinical series reported by clinical laboratories.…”
Section: Discussioncontrasting
confidence: 37%
See 1 more Smart Citation
“…This level of yield is similar to or slightly higher than those of previous reports, either in research studies 1,[5][6][7] or clinical series reported by clinical laboratories.…”
Section: Discussioncontrasting
confidence: 37%
“…The available evidence of the use of WES in a clinical setting has largely been an extension of a previous research protocol 1 or a comparison of traditional diagnostic methods and WES. 2 Here we report a series of our first 115 patients evaluated by WES as part of routine clinical care in our clinical genetic practice at a single institution.…”
Section: Introductionmentioning
confidence: 99%
“…Despite excellent coverage (96% of the reference genome at an average depth of 33X), the initial data assessment did not reveal a clear molecular diagnosis (19). A previously described (14) heterozygous DGKE nonsense mutation, c.966G.A (p.Trp322*), was found in patient II-1 by WGS and was subsequently confirmed by Sanger in all relatives except the mother (Supplemental Figure 4A).…”
Section: Identification Of a Second Family With The Dgke C888 +40a>gmentioning
confidence: 96%
“…Patient II-1 from family 2 underwent clinical WGS as part of the Genomics Medicine Clinic, in collaboration with Children's Hospital of Wisconsin and Froedtert Hospital (19). Twenty unrelated French patients with pediatric aHUS undergoing genetic screening in Paris were included in this study.…”
Section: Methodsmentioning
confidence: 99%
“…This paradigm shift in molecular analysis has been fully embraced in the endocrine field, both in research and at the clinic 28 . If the use of WGS in the clinical front has been so far limited to the diagnosis of severe complex phenotypes 29 , WES is now easily available as a diagnostic test and can be very useful for obtaining a molecular diagnosis in endocrinopathies for which several candidate genes exist, such as disorders of sex development 6,30 .…”
Section: Massive Parallel Sequencingmentioning
confidence: 99%